Treatment-related changes in psychopathy features and behavior in adolescent offenders - Caldwell, Michael F. (Criminal justice and behavior, 2012)
The impact of changes in psychopathy characteristics on institutional behavior was assessed in 127 incarcerated delinquent males who were treated in a specialized intensive treatment program. Participants were administered the self-report version of the Antisocial Processes Screening Device (APSD) on admission to the program and every 90 days through treatment. Changes in all APSD scales predicted improvement in institutional behavior and treatment involvement. For the 77 youth who had at least three administrations, repeated-measures analysis of variance showed significant changes in APSD total, Callous/Unemotional, Narcissism, and Impulsivity scores. For 127 youth who had at least two administrations and daily behavioral ratings, changes in each scale predicted improved institutional behavior and treatment compliance.